Analisis Pengaruh Tata Kelola Perusahaan, Karakteristik Perusahaan, dan Karakteristik Direktur Terhadap Penghindaran Pajak - Bianca, Tiffani Marla; Tang, Sukiantono (Faculty of Economics, Universitas Internasional Batam, 2018)
This research?s purpose is to analyze the effect of corporate governance, characteristic of companies, and characteristic of director toward tax avoidance. Corporate governance?s variables: board size, independent commissioner, managerial ownership, and concentrated ownership. Characteristic of companies? variables: company size, leverage, capital intensity, inventory intensity, and ROA. Characteristic of director?s variables: director?s term of office and age of the president. Tax avoidance uses 2 type of measurement: ETR and CETR. This study uses total 583 sample firms which are listed in Indonesia Stock Exchange from 2012 till 2016 or 2.915 observations data which selected using purposive sampling. ETR shows the result that board size and leverage have significant positive effect to ETR. Size and return on asset have significant negative effect to ETR. Independent commissioner, managerial ownership, concentrated ownership, capital intensity, inventory intensity, director?s term of office, and the age of the president have no significant effect to ETR. CETR shows the result that board size, inventory intensity, and return on asset have significant positive effect to CETR. Size and capital intensity have significant negative effect to CETR. Independent commissioner, managerial ownership, concentrated ownership, leverage, director?s term of office, and the age of the president have no significant effect to CETR.